Finite Element Approximations for Schrödinger Equations with Applications to Electronic Structure Computations (Journal of Computational Mathematics, 2018)
In this paper, both the standard finite element discretization and a two-scale finite element discretization for Schrödinger equations are studied. The numerical analysis is based on the regularity that is also obtained in this paper for the Schrödinger equations. Very satisfying applications to electronic structure computations are provided, too.
Keywords: Error analysis; Finite element; Eigenvalue; Quantum chemistry; Schrödinger equation; Two-scale.